Identification and therapeutic rescue of autophagosome and glutamate receptor defects in C9ORF72 and sporadic ALS neurons. - Shi, Yingxiao; Hung, Shu-Ting; Rocha, Gabriel; Lin, Shaoyu; Linares, Gabriel R; Staats, Kim A; Seah, Carina; Wang, Yaoming; Chickering, Michael; Lai, Jesse; Sugawara, Tohru; Sagare, Abhay P; et al. (JCI Insight, 2019)
Amyotrophic lateral sclerosis (ALS) is a fatal motor neuron disease with diverse etiologies. Therefore, the identification of common disease mechanisms and therapeutics targeting these mechanisms could dramatically improve clinical outcomes. To this end, we developed induced motor neuron (iMN) models from C9ORF72 and sporadic ALS (sALS) patients to identify targets that are effective against these types of cases, which together comprise ~90% of patients. We find that iMNs from C9ORF72 and several sporadic ALS patients share two common defects - impaired autophagosome formation and the aberrant accumulation of glutamate receptors. Moreover, we show that an anticoagulation-deficient form of activated protein C, 3K3A-APC, rescues these defects in both C9ORF72 and sporadic ALS iMNs. As a result, 3K3A-APC treatment lowers C9ORF72 dipeptide repeat protein (DPR) levels, restores nuclear TDP-43 localization, and rescues the survival of both C9ORF72 and sporadic ALS iMNs. Importantly, 3K3A-APC also lowers glutamate receptor levels and rescues proteostasis in vivo in C9ORF72 gain- and loss-of-function mouse models. Thus, motor neurons from C9ORF72 and at least a subset of sporadic ALS patients share common, early defects in autophagosome formation and glutamate receptor homeostasis and a single therapeutic approach may be efficacious against these disease processes.

Comparative genomic analysis of embryonic, lineage-converted and stem cell-derived motor neurons. - Ichida, Justin K; Staats, Kim A; Davis-Dusenbery, Brandi N; Clement, Kendell; Galloway, Kate E; Babos, Kimberly N; Shi, Yingxiao; Son, Esther Y; Kiskinis, Evangelos; Atwater, Nicholas; Gu, Hongcang; Gnirke, Andreas; et al. (Development, 2018)
Advances in stem cell science allow the production of different cell types either through the recapitulation of developmental processes, often termed 'directed differentiation', or the forced expression of lineage-specific transcription factors. Although cells produced by both approaches are increasingly used in translational applications, their quantitative similarity to their primary counterparts remains largely unresolved. To investigate the similarity between -derived and primary cell types, we harvested and purified mouse spinal motor neurons and compared them with motor neurons produced by transcription factor-mediated lineage conversion of fibroblasts or directed differentiation of pluripotent stem cells. To enable unbiased analysis of these motor neuron types and their cells of origin, we then subjected them to whole transcriptome and DNA methylome analysis by RNA sequencing (RNA-seq) and reduced representation bisulfite sequencing (RRBS). Despite major differences in methodology, lineage conversion and directed differentiation both produce cells that closely approximate the primary motor neuron state. However, we identify differences in Fas signaling, the Hox code and synaptic gene expression between lineage-converted and directed differentiation motor neurons that affect their utility in translational studies.
Keywords: Animals; Cell Lineage; Embryo, Mammalian; Epigenesis, Genetic; Genomics; Mice, Inbred C57BL; Motor Neurons; Pluripotent Stem Cells; Transcription, Genetic